Ethics and Economics. Ancient Ties and Incautious Assimilations (Nóema, 2012)
The crisis we are going through undermines the link between ethics and economics, bringing to light their common origins and deep contradictions. The crisis has shown us the fragility of an entire economic paradigm based on a dogmatic view which considers the utilitas as the sole purpose of human action. However, the "heart" of the problem is not about the need of a more ethical economics: it concerns a serious lack of political praxis which should be able to understand and manage a complex system which is vitiated by deep ambiguities and dangerous distortions.